HOW THE SOCIAL ENVIRONMENT MEDIATES FACTORS AFFECTING THE STUDENT'S INTENTION TO SAVE IN SHARIA BANK? - Rosita, Malikhatul Luthfi Dwi; Miranti, Titis (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
This study aimed to determine the effect of perception, religiosity, and knowledge on the intention to save in Islamic banks with social environment variables as mediation. This research is a type of quantitative research. Data analysis used in this study used the SEM (Structural Equation Modeling) analysis test. The population in this study were all 244 STAI Denpasar students. The sample used in this study used a purposive sampling method with 151 respondents. Research data was collected using a questionnaire. The results of this study indicate that the variables of perception, knowledge and social environment significantly affect the intention to save. In contrast, the religiosity variable does not significantly affect the intention to save. The social environment variables can mediate knowledge variables, while social environment variables cannot mediate perception and religiosity variables.